Kidney cachexia or protein‐energy wasting in chronic kidney disease: facts and numbers. Issue 3 (12th April 2019) - Koppe, Laetitia; Fouque, Denis; Kalantar‐Zadeh, Kamyar
Abstract: Background: Weight loss and homeostatic disturbances of both energy and protein balances are characteristics of several illnesses including cancer, heart failure, and chronic kidney disease (CKD). Different definitions have been used to describe this deleterious process. The term protein‐energy wasting (PEW) has been proposed for CKD patients by the International Society of Renal Nutrition and Metabolism . Methods: We searched the publication in Medline from February 2008 to September 2018 using PEW or cachexia in their title. Results: Since its inception, the term PEW has been exceptionally successful, highlighted by 327 original publications referenced in PubMed over 10 years. Using this classification, several studies have confirmed that PEW is among the strongest predictors of mortality in CKD patients [hazard ratio of 3.03; confidence interval of 1.69–5.26 in 1068 haemodialysis patients and 1.40 (1.04–1.89) in 1487 non‐dialysed patients across PEW stages 0 to 4]. Based on this classification, prevalence of PEW is 28% to 54% among 16 434 adults undergoing maintenance dialysis. PEW prevalence increases when renal function declines, that is, from <2% in CKD stages 1–2 to 11–54% in CKD stages 3–5. A more general definition of cachexia for all chronic diseases proposed by the Society on Sarcopenia, Cachexia and Wasting Disorders was also published concurrently. In the CKD area, we found 180 publications using 'cachexia' underlining that some confusion or overlap may exist. The definitions of PEW and cachexia are somewhat similar, and the main difference is that a loss of body weight >5% is a mandatory criterion for cachexia but supportive for PEW. Conclusions: The recent understanding of cachexia physiopathology during CKD progression suggests that PEW and cachexia are closely related and that PEW corresponds the initial state of a continuous process that leads to cachexia, implicating the same metabolic pathways as in other chronic diseases. Despite the success of the definition of PEW, using a more uniform term such as 'kidney disease cachexia' could be more helpful to design future research through collaborative groups of researchers with focus on cachexia.